New Chair Alliance - Katherine Frank; Dan Wheeler (Academic Chairpersons Conference Proceedings, 2017)
Those who will soon transition into a chair position or who have been a chair for two years or less will find this workshop particularly valuable. Topics covered include transitioning to new roles and responsibilities, annual planning, everyday management, strategic planning for the future, personal development, and finding satisfaction in being a chair and making a difference. Participants will gain practical tips and tools to improve effectiveness, become familiar with essential resources, learn how to identify an administrative mentor, as well as connect and network with others at a similar career stage.
Keywords: transitioning; new roles; management; strategic planning